Tashih and Tadhwif Method: A Study on Sunan Al-Mujtaba Annasa'i. - Kasan Bisri (Jurnal Hikmatuna, 2015)
This article aims to elaborate on and analyze the method of tashih and tadhwif for hadith used by an-Nasa'i, a muhaddith in the third century of the Hijra (codification era), in his book Sunan al-Mujtaba. The objective is to position an-Nasa'i among other muhaddithun. The article addresses three questions: first, what method does an-Nasa'i use in selecting and verifying hadiths? Second, to what extent is an-Nasa'i consistent in applying his method, and why is he considered a mutashaddid by scholars? Third, what are the unique aspects and qualities of an-Nasa'i's method of tashih and tadhwif? The research concludes several points. Firstly, an-Nasa'i formulated a set of criteria and principles for authentic hadiths, which he used to conduct tashih and tadhwif and verify the authenticity of each hadith. The criteria for authentic hadiths include trustworthy transmitters (tsiqqah), uninterrupted chain of transmission (ittisal), and absence of anomalies (syadz) and hidden defects (illat). Secondly, an-Nasa'i's consistency can be observed in three aspects: 1) his criticism of transmitters, 2) the use of specific wording in transmission, and 3) his annotations in al-Mujtaba. Thirdly, an-Nasa'i's strictness (tashaddud) sets him apart from others. This reflects his commitment to preserving hadiths from errors and deviations, which is a positive attribute. Similar efforts to minimize deviations were made by al-Bukhari through the requirement of liqa' for hadiths classified as sahih.